The stereology of the urinary bladder - Ulubay, Mahmut; Altun, Gamze; Kaplan, Arife Ahsen; Hamour, Hala Mahgoub; Kaplan, Süleyman (Nova Science Publishers, Inc., 2024)
Quantitative evaluation of the bladder wall structure can help evaluate pathological structures at morphological examination of the urinary bladder. Studies have applied stereological methods to radiological images and urinary bladder tissue specimen blocks embedded in paraffin. Volumetric evaluations of the bladder wall structure are particularly common. The wall structure of the urinary bladder consists of three layers, the epithelium plus lamina propria, muscular layer and adventitia/serosa layer. However, some studies also discuss the structure of the muscular mucosa and submucosa. The volume fractions of bladder wall components were calculated using a point-counting grid in a sample stereological study of the urinary bladder of diabetic rats. When the differences between the groups were subjected to statistical evaluation, no difference was observed between the groups in terms of the volume fraction of the mucosal layer, the muscular layer, or the serosa/adventitia layer. However, a remarkable increase was determined in the diabetes group at analysis of the ratio of blood vessels to the lamina propria (II) layer. These data were examined by considering the appropriate coefficient of error and coefficient of variation values. This chapter discusses in detail the stereological methods applied in the bladder and the histological structures examined, and the stereological results and restrictive steps of the sample study are also presented.
Keywords: Cavalieri Method; Point Counting Grid; Systematic Random Sampling; Urinary Bladder; Volume Fraction